PREVALENCE OF IRON DEFICIENCY ANEMIA AND ITS RISK FACTORS AMONG NURSING STUDENTS IN NURSING COLLEGE OF HYDERABAD - JAMALI , YA; SOOMRO , P; PANHYAR , AR; RUK , M; KHASKHELI , SA; AHMED , A (Biological and Clinical Sciences Research Journal, 2024)
Teens can have nutritional anemia by not getting enough iron, folate, or vitamin B1. Although many other nutritional anemia types can manifest, iron deficiency anemia is the most prevalent. Objective: The study aims to discover the prevalence of anemia and its risk factors among nursing students in the nursing college of Hyderabad. Methods: This cross-sectional study investigated the prevalence of iron deficiency anemia and associated risk factors among nursing students at the Nursing College of Hyderabad. It was conducted from March 15, 2024, until June 29, 2024. In a sterile environment, each subject had blood drawn by certified phlebotomists. Several hematological indicators were measured throughout the examination, including hemoglobin (Hb), serum ferritin, serum iron, total iron-binding capacity (TIBC), and transferrin saturation. Results: The overall frequency of iron deficiency anemia (IDA) was 42.0% among the students, with 215 individuals confirmed to be anemic. Of these pupils, 103 were male, and 112 were female, for 52.1%. The research discovered robust associations among college students between iron deficiency anemia (IDA) and several lifestyle and nutritional factors. Iron deficiency anemia (IDA) was statistically related to less consistent breakfast eating; 62.8% of IDA students reported this, compared to 37.2% of students who reported regular breakfast consumption. This correlation was statistically significant, with a p-value of 0.012. Furthermore, there was a notable correlation between the intake of vegetables and fruits and the occurrence of IDA (p = 0.03). Conclusion: The study discovered that 42.0% of apparently healthy young nursing students in the sample had iron deficiency anemia (IDA). The study also found that insufficient iron intake, frequent tea drinking, frequent consumption of red meat, and a previous history of iron deficiency anemia were the top risk factors for developing anemia.